2006
DOI: 10.1093/hmg/ddl164
|View full text |Cite
|
Sign up to set email alerts
|

Ataxin-3 binds VCP/p97 and regulates retrotranslocation of ERAD substrates

Abstract: Expansion of a polyglutamine tract in ataxin-3 (AT3) results in spinocerebellar ataxia type 3/Machado-Joseph disease, one of the nine polyglutamine neurodegenerative diseases. Understanding the normal functions of AT3 as well as its function in the context of expansion of the polyglutamine tract is critical for understanding the disease process. AT3 is a deubiquitylating enzyme with limited information on its cellular functions. We find that transfecting cells with AT3 increases cellular levels of endoplasmic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
217
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(229 citation statements)
references
References 53 publications
8
217
0
Order By: Relevance
“…We provide mechanistic insight into this specific defect: Toxic polyQ-expanded proteins en-trap the ERAD proteins Ufd1, Npl4, and p97 (VCP) and thereby inhibit their essential participation in ERAD. Our results explain the molecular basis of the previously reported polyQ-induced unfolded protein response (UPR) and ER stress (Kouroku et al 2002;Nishitoh et al 2002;Thomas et al 2005) and, as noted in the Discussion, suggest that toxicity may be related to the normal function of SCA3 (Zhong and Pittman 2006). Further, we document that the dysfunction in ER protein homeostasis occurs with high specificity and is an early response, the first we detected after the expression of polyQ-expanded htt exonI.…”
supporting
confidence: 86%
“…We provide mechanistic insight into this specific defect: Toxic polyQ-expanded proteins en-trap the ERAD proteins Ufd1, Npl4, and p97 (VCP) and thereby inhibit their essential participation in ERAD. Our results explain the molecular basis of the previously reported polyQ-induced unfolded protein response (UPR) and ER stress (Kouroku et al 2002;Nishitoh et al 2002;Thomas et al 2005) and, as noted in the Discussion, suggest that toxicity may be related to the normal function of SCA3 (Zhong and Pittman 2006). Further, we document that the dysfunction in ER protein homeostasis occurs with high specificity and is an early response, the first we detected after the expression of polyQ-expanded htt exonI.…”
supporting
confidence: 86%
“…involved in the degradation of mutant neuroserpin strongly suggests that VCP/p97 cooperates with Hrd1 and gp78 for neuroserpin degradation. The N-terminal fragments of polyQ-expanded huntingtin (Nhtt) and ataxin-3 inhibit the function of ERAD and retrotranslocation (33,34). In our observations, we also found that the polyQ-expanded Nhtt or ataxin-3 significantly stimulates mutant neuroserpin aggregation and perturbs its proteasomal degradation (data not shown).…”
Section: Discussionmentioning
confidence: 56%
“…In our observations, we also found that the polyQ-expanded Nhtt or ataxin-3 significantly stimulates mutant neuroserpin aggregation and perturbs its proteasomal degradation (data not shown). As the polyQexpanded Nhtt and ataxin-3 affect ERAD by influencing the VCP complex (33,34), and VCP deficiency significantly decreases mutant neuroserpin degradation rates (Fig. 2D), these data further suggest that the ERAD machinery is involved in mutant neuroserpin degradation.…”
Section: Discussionmentioning
confidence: 76%
“…For example, ataxin-3 interacts with ubiquitinproteasome pathway components (32)(33)(34), localizes to protein inclusions in various disease states (35,36), regulates the formation of aggresomes (37), and assists in degrading substrates retrotranslocated from the endoplasmic reticulum (34,38). In Drosophila, wild type ataxin-3 can suppress polyQ-mediated neurodegeneration through its ubiquitinbinding and cleavage activities, and expanded ataxin-3 retains this suppressor activity despite its pathogenic mutation (39).…”
mentioning
confidence: 99%